Increased hepatic inflammation in a normal-weight mouse after long-term high-fat diet feeding - Toita, Riki (J Toxicol Pathol, 2017)
Among five C57BL/6 mice fed a high-fat diet (HFD) for 12 weeks, one mouse showed a body weight (BW) similar to normal diet (ND)-fed mice. We compared obesity-related parameters of three groups (ND-fed mice, one HFD-fed normal-weight mouse, and HFD-fed overweight mice), including visceral fat weight, serum levels of total cholesterol (TC), glucose, and aminotransferases (AST and ALT), adipocyte size, percentage of crown-like structures, severity of hepatic steatosis, and number of inflammatory foci. Compared to ND-fed mice, the HFD-fed normal-weight mouse exhibited a similar visceral fat weight, similar serum levels of glucose and aminotransferases, and a similar percentage of crown-like structures. On the other hand, the serum TC level, adipocyte size, and hepatic steatosis severity of the HFD-fed normal-weight mouse were intermediate between those of ND-fed mice and HFD-fed overweight mice. Interestingly, the number of hepatic inflammatory foci in the HFD-fed normal-weight mouse was remarkably increased compared with those in HFD-fed overweight mice. These results suggest that having BW or serum ALT levels within normal ranges may not guarantee absence of hepatic inflammation and that the HFD-fed normal-weight mouse can be used as an animal model for the study of liver inflammation, particularly in patients with normal BWs and/or serum ALT values.